Feeding questions of organic lamb fattening - Monori, István; Fehér, Alajos; Czimbalmos, Róbert (Acta Agraria Debreceniensis, 2009)
Organic farming has done in line with conventional farming in the Karcag Research Institute of DU CASE since 2001. Our organic farming activities were enhanced with sheep farming and grassland management in 2005. We started our study of technology development of organic lamb fattening and the treatment of its economic effect this year. Our goal was to develop the elements of the technology to reach a more efficient organic lamb fattening. We also studied what economic advantages the organic sheep farming could realize in the present economic environment. Our studies were carried out between 2005 and 2007. We established that the excellent ewe feeding (good quality of fodder and silage) can decrease the lamb feeding cost between the 2nd and 8th weeks of the lambs’ life. We established that the yield of convention lambs are significantly higher than the yield of organic lambs. The cost of organic lamb fodder is significantly lower than the cost a convention lamb fodder, but the profit was higher in the case of convention lamb fattening. The organic lamb fattening technology (without extra price) is not competitive to the conventional lamb fattening technology. We think that the profitability of organic lamb fattening is significantly less than of the convention one. The organic lamb price should be 20-30% higher than the other price to be competitive. Unfortunatly there is only a little demand for organic lamb and there is no difference between the prices of organic and convention lambs, so organic sheep farmers have worse economic circumstances than conventional sheep farmers.